2012
DOI: 10.4172/2155-6148.1000225
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Effectiveness of Budesonide Inhalation in Reducing Postoperative Throat Complaints

Abstract: Objective: To evaluate the efficacy of budesonide suspension inhalation in reducing the incidence and severity of postoperative sore throat (POST) and hoarseness induced by tracheal intubation.Methods: 120 patients scheduled for thyroid surgery with general anaesthesia were randomized into 3 groups. Group A received 200 mcg budesonide inhalation suspension (BIS) 10 min prior to the tracheal intubation and received the same treatment 6 h and 24 h after extubation. Group B received 200 mcg BIS 6 h and 24 h after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The incidence was lower in budesonide group at 48 hrs as compared to other groups. It is thought that topical corticosteroids decrease irritation, inflammation, and edema in the upper airways as well as the incidence and severity of sore throat and cough (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence was lower in budesonide group at 48 hrs as compared to other groups. It is thought that topical corticosteroids decrease irritation, inflammation, and edema in the upper airways as well as the incidence and severity of sore throat and cough (13).…”
Section: Discussionmentioning
confidence: 99%
“…The patients were familiarised with the concept of visual analogue scale (VAS) for pain assessment with 0 = no pain and 10 = worst possible pain in pre anaesthetic checkup. Pain was classified as no pain (VAS=0), mild (1-3), moderate (4-6) and severe (7)(8)(9)(10). The condition of laryngopharynx was assessed by an ENT surgeon on indirect laryngoscopy at interval of 1, 6 and 24 hrs using the signs of mucositis in laryngopharynx (8).…”
Section: Methodsmentioning
confidence: 99%
“…The inhalational route had the advantage of reduced systemic side effects compared to the parenteral route because of limited systemic absorption. A study performed by Chen et al [33] concluded that the use of prophylactic inhaled budesonide can decrease the incidence and severity of POST and hoarseness of the voice after general anesthesia among patients undergoing thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It also has the advantages of rapid onset, good curative effect, convenient use, less side effects, etc., and has thus become one of the most commonly used methods for the treatment of respiratory diseases. [4,5] There are three types of medical nebulizers including the pneumatic nebulizer, the ultrasonic nebulizer, and the vibrating-mesh nebulizer. Oxygen delivery devices with a pneumatic nebulizer function are widely used in Japan [6] ,China [8] and the world [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Aerosol inhalation is a commonly used method for the clinical treatment of acute exacerbation of COPD. [4,5] Pneumatic nebulizers are commonly used in clinics and are usually connected to the central oxygen supply system of the hospital; also called an oxygen nebulizer. [6] Pneumatic atomizer models are diverse, however, there are no literature reports on the use of pneumatic nebulizers with respect to drug wastage.…”
Section: Introductionmentioning
confidence: 99%